Improvement of MoS2 Film Quality by Low Flux of Sputtered Particles Using a Molybdenum Grid - Shinya Imai; Ryo Ono; Iriya Muneta; Kuniyuki Kakushima; Tetsuya Tatsumi; Shigetaka Tomiya; Kazuo Tsutsui; Hitoshi Wakabayashi (IEEE Journal of the Electron Devices Society)
Lowering the flux of sputtered particles using a molybdenum grid reduced the deposition rate of MoS2 films with an enlargement of the grain size measured by in-plane X-ray diffraction. The MoS2 film crystallinity evaluated by the Raman spectroscopy was improved because the S/Mo ratio was also enhanced by the low-rate sputtering. In addition, the enhancement of the grain size was confirmed from plan-view TEM observations of MoS2 films, consistent with the in-plane XRD results. Therefore, reducing the particle flux during sputtering is expected to contribute to the better-quality MoS2 films for pn-stacked 2D-CMOS devices and human interface devices.